2010
DOI: 10.2135/cropsci2009.10.0635
|View full text |Cite
|
Sign up to set email alerts
|

Drought Response and Recovery Characteristics of St. Augustinegrass Cultivars

Abstract: As water resources become restricted for use on amenity turfgrass systems, the inability for consumers to delineate incremental drought stress relating to plant health can result in the misuse of water resources during drought conditions. Seven cultivars of St. Augustinegrass (SA) [Stenotaphrum secundatum (Walt.) Kuntze] and two root zone depths were evaluated for drought response and recovery during consecutive 60‐d drought and 60‐d recovery periods over 2 yr. Using digital image analysis, drought response an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 12 publications
7
37
2
1
Order By: Relevance
“…Comparable to other studies Richardson et al, 2008;Steinke et al, 2010Steinke et al, , 2011, scatter plots of the GTC percentage versus number of days of the water deficit periods and number of days of the spring green-up periods indicated a strong non-linear relationship. GTC data fitted well to the sigmoid variable slope model:…”
Section: Statistical Analysescontrasting
confidence: 77%
See 1 more Smart Citation
“…Comparable to other studies Richardson et al, 2008;Steinke et al, 2010Steinke et al, , 2011, scatter plots of the GTC percentage versus number of days of the water deficit periods and number of days of the spring green-up periods indicated a strong non-linear relationship. GTC data fitted well to the sigmoid variable slope model:…”
Section: Statistical Analysescontrasting
confidence: 77%
“…The importance of substrate depth in turfgrass survival during extended periods of drought has also been documented by other researchers. Steinke et al (2010) evaluated drought response of seven cultivars of St. Augustinegrass under restricted (10 cm) and unrestricted soil depth during a consecutive 60-day drought period using digital image analysis. They reported that at a 10 cm depth none of the cultivars of the study survived and that turfgrass sward was completely browned off over a 6-12-day period during the first study year and within 10-20 days in the second study year, while all entries survived when planted in unrestricted soil depth and subjected to the same drought level.…”
Section: -D-h 4-d-h 2-d-h 5-d-h 1-d-h 6-d-h 3-d-l 4-d-l 1-d-l 3-s-h mentioning
confidence: 99%
“…Consumers' inability to distinguish between drought stress and grass survival and their expectations of stay‐green grass often lead to the misuse of water sources such as excessive irrigation (Steinke, Chalmers, Thomas, & White, ). To determine the best management practice regarding irrigation and to direct consumer expectations following drought conditions, drought studies were conducted in San Antonio, TX (Steinke, Chalmers, Thomas, White, & Fipps, ; Steinke et al., ). In a 60‐day drought period, St. Augustinegrass [ Stenotaphrum secundatum (Walt.)…”
Section: Introductionmentioning
confidence: 99%
“…In a 60‐day drought period, St. Augustinegrass [ Stenotaphrum secundatum (Walt.) Kuntz] cultivars demonstrated great variation in days of losing 50% green cover (from 23 to 60 days) (Steinke et al., ). When irrigation resumed, cultivars exhibited a 52‐day difference in recovering to 50% green cover.…”
Section: Introductionmentioning
confidence: 99%
“…This is a valuable trait for use in lawns, particularly in smaller residential landscapes where trees are dominant, as is the case in many neighborhoods throughout North Carolina. Furthermore, St. Augustinegrass has good salt, heat, and to a moderate extent, drought tolerance (Steinke et al 2010). These characteristics, in conjunction with its relatively low input requirements, make this species a very desirable turfgrass for the southeastern United States.…”
mentioning
confidence: 99%